CT‐Guided Percutaneous Infrazygomatic Radiofrequency Neurolysis Through Foramen Rotundum to Treat V2 Trigeminal Neuralgia - Huang, Bing; Yao, Ming; Feng, Zhiying; Guo, Jianguo; Zereshki, Arzhang; Leong, Michael; Qian, Xiang (Pain medicine (Malden, Mass.), 2014)
Objective Percutaneous radiofrequency thermocoagulation or neurolysis of Gasserian ganglion through foramen ovale (FO) is the classical approach to treat trigeminal neuralgia (TN). However, it has been technically challenging when individual trigeminal sub‐branch nerve block is desired through this approach. We have thus developed a novel computed tomograph‐guided technique to block the V2 trigeminal nerve through foramen rotundum (FR). With this technique, we have conducted a study of 27 patients with isolated V2 TN. We hypothesize that this new technique will have comparable clinical outcome with the conventional FO approach. Design Prospective study. Setting Academic hospitals. Subjects Twenty‐seven patients with isolated classical V2 TN were enrolled and divided into FO group (N = 12) and FR group (N = 15). Methods Numeric Rating Scale (NRS) scores for facial pain, at pretreatment, immediate postoperative, postoperative 1 day, and 1, 6, and 12 months were recorded. The primary clinical outcome (successful pain relief with 50% or more reduction in NRS) and secondary adverse clinical outcome (hematoma, facial numbness, masticatory weakness, and corneal involvement) were compared and analyzed. Results Both groups have good immediate and sustained pain relief. However, when compared with the FO group, the FR group is associated with shorter procedural time (29.2 ± 9.3 vs 45.4 ± 22.13 minutes, P < 0.05), has less nonspecific block in V1 and V3 dermatomes, and has fewer adverse outcomes including masticatory weakness (0/15 vs 5/12) and corneal perforation (0/12 vs 1/15). Conclusions We have developed a novel technique to selectively block the V2 trigeminal nerve at FR. This novel FR approach may be a good alternative to the classical FO approach when an isolated V2 branch block is desired.